2014
DOI: 10.1007/s10067-014-2602-6
|View full text |Cite
|
Sign up to set email alerts
|

Clinical evaluation of R202Q alteration of MEFV genes in Turkish children

Abstract: To date, over 200 alterations have been reported in Mediterranean fever (MEFV) genes, but it is not clear whether all these alterations are disease-causing mutations. This study aims to evaluate the clinical features of the children with R202Q alteration. The medical records of children with R202Q alteration were reviewed retrospectively. A total of 225 children, with 113 males, were included. Fifty-five patients were heterozygous, 30 patients were homozygous for R202Q, and 140 patients were compound heterozyg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
23
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 15 publications
3
23
0
2
Order By: Relevance
“…To date, FMF phenotype has been linked, by several groups, with R202Q alteration 5 6 13 14. The presence of R202Q homozygosity in both of our FMF patients is in parallel with previous findings from our group where almost 10% of Greek FMF patients carry only this mutation, which is extremely rare in the healthy Greek population 5 6.…”
Section: Discussionsupporting
confidence: 88%
“…To date, FMF phenotype has been linked, by several groups, with R202Q alteration 5 6 13 14. The presence of R202Q homozygosity in both of our FMF patients is in parallel with previous findings from our group where almost 10% of Greek FMF patients carry only this mutation, which is extremely rare in the healthy Greek population 5 6.…”
Section: Discussionsupporting
confidence: 88%
“…R202Q was first identified by Bernot and colleagues and has been described as a benign polymorphism (Bernot et al, 1998). Besides, R202Q (c.605GNA) was described as a frequent polymorphism, and the G allele was found to be in linkage disequilibrium (LD) with M694V in Infevers Database (Touitou et al, 2004 (Giaglis et al, 2007;Yigit et al, 2012;Comak et al, 2014). The clinical significance of the R202Q alteration in Turkish pediatric patients has been published in a paper.…”
Section: Discussionmentioning
confidence: 94%
“…R202Q in the MEFV gene has been reported to lead to symptoms consistent with the clinical findings of FMF in some patients, and the author suggested that the R202Q alteration was probably a mutation rather than a polymorphism, but it might be associated with a mild phenotype and could show phenotypic differences similar to the common MEFV mutations. Moreover, it has been suggested that patients with homozygous R202Q alteration (or R202Q with another MEFV mutation) may require colchicine treatment (Comak et al, 2014). In addition, Yigit et al reported a high association between the MEFV gene R202Q polymorphism and FMF.…”
Section: Discussionmentioning
confidence: 98%
“…1 Besides, exon 2 mutations including E148Q and R202Q have been reported to be associated with the mildest disease with least penetrance. 22,23 A recent study that were carried out on 104 febrile seizure patients by Ozen et al reported that MEFV gene mutations, especially M694V mutation, are positively associated with febrile seizures. 24 In the same study they also showed that of the 104 patients 68 of them were heterozygotes for any mutation and 10 patients were compound heterozygotes (4 patients for E148Q/ M694V and 6 patients for M694V/V726A).…”
Section: Discussionmentioning
confidence: 97%